Awareness within local authorities in England of autism spectrum diagnoses of looked‐after children. (15th October 2018) - Parsons, Sarah; McCullen, Alice; Emery, Tracey; Kovshoff, Hanna
Abstract : Educational outcomes for looked‐after children on the autism spectrum are significantly poorer than for autistic children not being looked‐after by their local authority (those 'in care'), and poorer than for most other groups of children with special educational needs who are looked‐after in England. Such poor outcomes have led to calls for specific attention to be paid to the needs of autistic looked‐after children within the care of local authorities. There is also evidence that the numbers of autistic children being looked‐after by local authorities could be under‐represented in official figures. This study sought to find the current numbers of autistic looked‐after children formally recorded across local authorities in England, and whether their needs are given special attention via strategic planning and oversight, using freedom of information (FoI) requests sent to all local authorities in England. From the 147 (97%) local authorities who responded, approximately 3% of looked‐after children in England are recorded as having an autism spectrum diagnosis, although this is still very likely to be an underestimation. The majority of local authorities do not routinely monitor or report on the diagnostic status of autistic looked‐after children at a strategic level. Implications for research and practice are discussed.